Analisis Sistem Pembelian Barang Dan Jasa Di Rumah Sakit Ali Sibroh Malisi Tahun 2024 - Dewi, Intania Prima (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
The Procurement Department or what is often also called the Purchasing Department and Finance Department is a non-medical field that plays a role in supporting hospital operations. The system for purchasing goods and services at Ali Sibroh Malisi Hospital is based on purchasing routine goods, inventory of goods and replacement goods/spare parts. This research was conducted at Ali Sibroh Malisi Hospital in 2024. This research is a qualitative descriptive research with the type of data used being primary data in the form of interviews and secondary data in the form of direct observation and document review. Informants in this research included the procurement unit coordinator, AR/AP staff, head of finance and finance and accounting manager at Ali Sibroh Malisi Hospital. This research includes input variables consisting of human resources, policies and SOPs, systems, facilities and infrastructure. The process variables consist of demand, purchase price offers and supplier selection, purchase orders, goods receipt, debt recording, purchase payments. The output variable is the availability of goods and services at Ali Sibroh Malisi Hospital. The results of research on the system for purchasing goods and services in hospitals in 2024 show that the system used at Ali Sibroh Malisi Hospital does not yet use the Hospital Information System as a whole in non-medical units. It is hoped that Ali Sibroh Malisi Hospital will use SIMRS for all units in its system for purchasing goods and services and fix existing problems, so that the goods and services needed at Ali Sibroh Malisi Hospital can be fulfille